Orforglipron as a Small-Molecule GLP-1 Receptor Agonist: A New Era of Incretin-Based Oral Therapy? - Blecharczyk, Małgorzata; Jakimowicz, Aleksandra; Kamińska, Zuzanna Zofia; Malcher, Aleksandra; Mrozek, Martyna; Pacanowska-Trawnicka, Martyna; Zielińska, Agnieszka; Zydlewski, Igor (Quality in Sport, 2026)
Introduction: Facing the increasing number of people suffering from obesity, overweight and weight-related comorbidities, the development of medications that support weight loss is crucial. The currently available therapies based on glucagon-like peptide receptor 1 agonists (GLP-1 RAs) and glucose-dependent insulinotropic polypeptide/GLP-1 RAs allow for weight loss of 8-21% [1]. However, a significant factor reducing treatment adherence is subcutaneous route of administation by injection, as well ass - in the case of oral semaglutide – restrictive dosing requirements: the drug need to be taken at least 30 minutes before the first meal, beverage, or other oral medication in the morning and with no more than 120 ml of plain water [2]. Aim of the study: The purpose of this study is to review the safety and tolerance of orforglipron and to compare it with oral semaglutide based on ACHIEVE-3 clinical trail. Material and Methods: Review and analysis of randomised clinical trials available on PubMed. We excluded phase 1 trials in analysis of patients with obesity without diabetes mellitus and patients with DM2. Notably, main clinical trials focusing on orforglipron were funded or supported by Eli Lilly and Company. Conclusions: Orforglipron is definitely promising as a small-molecule GLP-1 receptor agonist. The therapy is effective in body weight reduction and results in a significant, dose-dependent reduction in HbA1c levels. With significant effect on weight loss, cardiometabolic parameters and improvement in glycemic profile, it can be used in combination with a reduced-calorie diet and increased physical activity in adults, as a weight-loss therapy or in patient with type 2 diabetes. However, all of the studies published so far on the innovative molecule of orforglipron were based on limited number of patients, therefore long-term safety, tolerance in a larger population and general long-term impact of orforglipron on health needs extensive studies.